2013
DOI: 10.3354/meps09992
|View full text |Cite
|
Sign up to set email alerts
|

Diet richness of invasive Indo-Pacific lionfish revealed by DNA barcoding

Abstract: Indo-Pacific lionfish Pterois spp. have recently invaded marine habitats throughout the western Atlantic, Gulf of Mexico, and Caribbean Sea. Their unusual hunting behaviour suggests that they could prey on most fish species within their gape size limits. However, few prey species have been identified so far due to the challenges of identifying partly digested prey. Moreover, it is not clear how well the identifiable diet reflects the unidentified portion. To address these issues, we DNA-barcoded unidentifiable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 33 publications
3
73
0
2
Order By: Relevance
“…In total, 22 families of teleosts (44 species) and 14 families of crustaceans (17 species) were found in the stomach contents of lionfish in Bermuda. This substantial contribution of both teleosts and crustaceans, with a broad range of families and species in each category, supports the prevailing view that lionfish are generalist and opportunist predators (Muñoz et al 2011, Layman & Allgeier 2012, Côté et al 2013. The contribution of key prey items was fairly consistent across the indices of importance, at the species and family level, and when considering trophic guild (Table 3).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In total, 22 families of teleosts (44 species) and 14 families of crustaceans (17 species) were found in the stomach contents of lionfish in Bermuda. This substantial contribution of both teleosts and crustaceans, with a broad range of families and species in each category, supports the prevailing view that lionfish are generalist and opportunist predators (Muñoz et al 2011, Layman & Allgeier 2012, Côté et al 2013. The contribution of key prey items was fairly consistent across the indices of importance, at the species and family level, and when considering trophic guild (Table 3).…”
Section: Discussionsupporting
confidence: 65%
“…Taken together, these data suggest that if the lionfish population in Bermuda continues to expand, there will likely be no spatial or temporal refuge for potential lionfish prey, which may eventually include any juvenile or small-bodied fishes or crustaceans. This, in turn, suggests that the impacts of invasive lionfish may eventually be felt across a broad range of species and habitats, as has indeed been suggested by other studies (see for example Muñoz et al 2011, Côté et al 2013). …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This technique discards useful information that could be obtained in the digested portion of the stomach contents (the liquids or digested pulp). However, the traditional morphological method is widely applied (Albins & Hixon 2008, Morris & Akins 2009, Alexander & Haynes 2011, Jud et al 2011, Muñoz et al 2011, Green et al 2012, Frazer et al 2012, Layman & Allgeier 2012, Green & Côté 2014, while the more accurate DNA barcoding approach has been less frequently used (Barbour et al 2010, Valdez-Moreno et al 2012, Côté et al 2013. Despite the higher resolution attained with this approach, traditional DNA barcoding also has disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also observed individual lionfish consuming up to 20 small fish in a single 30-minute period, and eating prey with body lengths two thirds of their own. Work by Côté et al (2013) indicates that the predator may consume more than half of the potential prey species on invaded reefs, and the impacts on native reef fish populations may yet prove to be severe. Given the intricacies of coral reef trophic interactions, such impacts can rapidly cascade to induce ecosystem-level effects, with Lesser and Slattery (2011) showing that lionfish predation is likely to be the driver of an observed phase shift from coral domination to algal domination on mesophotic reefs that may provide stability and refuge from disturbance for shallower reefs .…”
Section: Introductionmentioning
confidence: 99%